Numerical Analysis of Aluminium Extraction from Packaging Waste Utilizing Arc Plasma - Chung, Jindo; Seomun, Jun; Kim, Jangwoo (Asian Journal of Chemistry, 2014)
This study is a preliminary study for the pre-design of thermal recycle gasification melting furnace. This study is aimed to reduce the impediments during actual operation, derive the basic design factors for economic design through numerical analysis and to obtain data to establish operating variables. This study conducted a numerical analysis under different plasma torch temperature conditions such as 2600, 2800, 3000 and 3200 K. The result showed that when the temperature conditions are 2,600 and 2,800 K, the high temperature formed in A area near the plasma torch are not delivered to the entire furnace or evenly distributed and a local low temperature zone is formed around C zone since complete mixture with the internal fluid did not occur due to the inducement of the oxygen at room temperature. This occurred in both conditions because the temperature required for firing reaction did not reach 1620 K, which is expected to disturb the smooth processing in aluminum extraction and reducing the time required to form the ambient temperature in the furnace. On the contrary, when the plasma torch temperatures are 3000 and 3200 K, the temperature inside the furnace is evenly distributed at 1700 K or above. It is considered that there is no solidification problem in aluminum melting and firing reaction in both condition.